Mapping the oxygen structure of γ-Al2O3 by high-field solid-state NMR spectroscopy - Qiang Wang (Nature Portfolio, 2020)
γ-Al2O3 is widely used in catalytic processes, but understanding its detailed structure remains a challenge. The authors, using two-dimensional solid-state NMR spectroscopy at a high magnetic field, characterize the spatial proximity and connectivity between oxygen species from the bulk to the surface.